Correlation of Nurse Therapeutic Communication to Family Anxiety while Waiting for Child Patients in the Inpatient Room - Subairi, Moh; Muhith, Abdul (Chakra Brahmanda Lentera Institute, 2024)
Background: Anxiety is often found in families whose children are hospitalized and hospitalized. This is because they are unable to build support for clients and they often see families having difficulty working with nurses or health workers. The aim of the research was to examine the relationship between family anxiety and the therapeutic communication of nurses in the inpatient room of the Klampis Health Center, Bangkalan Regency, Madura, while the patients were pediatric patients. Methods: Analytical correlational research design. Purposive sampling was used to select a large sample of 70 responders. Therapeutic communication is the independent variable, and anxiety is the dependent variable. Patients were given anxiety questionnaires and nurse therapy communication tools for data collection. Apply the Spearman Rank test to your analysis. Results: The results of the study of 70 respondents, most of the respondents amounted to 46 (65.7%) respondents stated that the nurse's therapeutic communication was good and not anxious when waiting for pediatric patients in the Inpatient Room of the Klampis Health Center, Bangkalan Regency, Madura. after a spearman rank test with a significance value of 0.000 and a correlation coefficient of 1.000, which means that there is a perfect correlation between nurse therapeutic communication and family anxiety while waiting for pediatric patients in the Inpatient Room of the Klampis Health Center, Bangkalan Regency, Madura. Conclusion: Nurses in the inpatient room who have good therapeutic communication can reduce the anxiety of the patient's family when their children are treated in the Inpatient Room of the Klampis Health Center, Bangkalan Regency, Madura. Her advice for nurses or health workers is expected to always provide good therapeutic communication in order to create a calm and comfortable atmosphere at the Public Health Center.